Outcomes of Laparoscopic Gastric Greater Curvature Plication in Morbidly Obese Patients - N. Khidir; M. Al Dhaheri; W. El Ansari; M. Al Kuwari; D. Sargsyan; M. Bashah (Hindawi Limited, 2017)
Background. Laparoscopic gastric greater curvature plication (LGGCP) is a restrictive bariatric procedure without gastrectomy. However, limited literature on effectiveness of gastric plication exists. Objectives. We assessed LGGCP's efficacy, effects on associated comorbidities, safety and the rate of complications, and patient satisfaction with LGGCP's outcomes among morbidly obese patients. Method. Analysis of retrospectively data collected from medical records of 26 patients who had undergone LGGCP at Hamad General Hospital, Qatar, during 2011-2012. Results. Most patients (92%) were Qatari nationals. The sample's mean age was 35.1 years. Mean duration of hospital stay was 3.9±1.2 days. Mean preoperative BMI was 40.7 kg/m2 that decreased at 2 years to 34.6 kg/m2. LGGCP's effects on comorbidities were such that 7.6% of patients experienced resolutions of their comorbidities. There were no mortality or postoperative complications that required reoperation. Six patients (23%) were satisfied with the LGGCP's outcomes while 10 patients (38.5%) underwent sleeve gastrectomy subsequently. Conclusion. LGGCP had acceptable short term weight loss results, exhibited almost no postoperative complications, and improved patients' comorbidities. Despite the durability of the gastric fold, some patients regained weight. Future research may assess the possibility of an increase in the gastric pouch size postplication associated with weight regain.